TEST OF THE YIELD OF n-HEXANA, ETIL ACETATE AND BUTANOL FRACTIONS IN SEA GRAPE (Caulerpa lentillifera) - Elga Nurul Adha; N. Ira Sari; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aims to determine the yield of each fraction of sea grape extract (Caulerpa lentillifera) with solvents based on the level of polarity.The research method used was an experiment by conducting a series of experiments by extracting and fractionatingC. lentillifera sea grapes with solvents of different polarity, namely n-hexane, ethyl acetate and butanol.The parameter test was yield value of the extract fraction in C. lentillifera.. The result showed that the highest yield was obtained from non polar solvent in hexane fraction 0.42%, followed by semi polar solventin ethyl acetate fraction 0.33% and non polar solvent in butanol fraction 0.31%. Therefore, the yield of sea grape is more optimal extracted using non polar solvent n hexane fraction than semi polar etyl ecetate and polar solvent butanol fraction.Keywords: Sea grape (Caulerpa lentillifera), Extraction, Fractionated, Yield